Digitalization In The Financial Statements: Study In Trini Karya Social Business - Awan Santosa; Rina Dwiarti; Audita Nuvriasari; Eno Casmi; Mohd Fadhil Harfiez Abdul Muttalib (International Journal Of Community Service, 2022)
Trini Karya is one of the driving forces for the family economy in the Trini hamlet whose existence must be supported by intellectuals so that its business continues to develop and grow. Mercu Buana University Yogyakarta is one of the campuses that has contributed tothe development of Trini Karya through service programs. This service aims to be able to help describe the problems that occur in the Trini Karya Business Unit, where one of the problems that arise is problems in the field of financial reporting. In the Trini Karya business unit, the problems are unstructured financial reporting, knowledge of financial reports and the ability of Trini Karya members to perform digital financial reports. Based on these problems, several things that can be a solution are to disseminate information about making financial reports simpler so that Trini Karya members can easily understand how to make financial reports. In addition, Trini Karya members or management are also given socialization regarding the use of digital financial reports, the goal is to use digital financial reports, which are expected to be able to make financial reports easier and more structured. After that, members and administrators are given training on the practice of making financial reports and making financial reports digitally using software that can be accessed by members or administrators of Trini Karya. After that, assistance was provided to the Trini Karya management in relation to digital financial reporting. The expected output target of this program is, it is hoped that Trini Karya will be able to make digital financial reports more accurately, structured and well-scheduled.